CONCEPT, LEGAL BASIS OF FINANCIAL INVESTIGATION ON THE CASES OF MONEY LAUNDERING AND STAGES OF FORMATION (World Bulletin of Management and Law, 2023)
In recent years, the term "financial investigation" is frequently encountered not only in foreign, but also in the national law enforcement system
Keywords: system; financial; encountered